Plant callus response to egglaying by chorus cicada and its effect on egg hatch - Rowe, C.A.; Logan, D.P.; Connolly, P.G. (New Zealand Plant Protection, 2016)
Chorus cicada Amphipsalta zelandica (Biosduval) is an endemic species of cicada that is a pest of kiwifruit Adult female cicadas cause damage to kiwifruit canes when egg laying The oviposition wound often stimulates the local formation of callus tissue in kiwifruit canes The effect of eggnest callusing on the proportion of eggs to hatch successfully was investigated as a potential plant resistance trait for selection The proportion of callus tissue covering the eggnest and the number of eggs hatched were measured from eggnests in canes of two kiwifruit cultivars Hayward and Zesy002 and stems of Hass avocado Eggnests with more callus tissue had reduced egg hatch in both cultivars of kiwifruit and avocado The host plant also affected egg hatch with significantly different hatch rates between the two kiwifruit cultivars and avocado at zero percent callusing